Towards critical literacy : literature and teachers' reactions to reader-response theories : a thesis presented in fulfilment of the requirements for the degree of Master of Arts in Second Language Teaching at Massey University - Brown, R. A. Julie (Massey University, 1999)
Much poststructuralist literary theory, in particular that derived from reader-response theories, points to the need for the development in readers of a more critical literacy. Earlier researchers and educators in the field of reader-response theories, indicated a move away from the New Critics' structuralist focus on the author's intention and a text-based meaning, to acknowledge the active role of the student/reader in the creation of meaning. Enlarging on the subjective role of the student/reader, later researchers, in particular the Social and Cultural theorists, introduced a more critical element by focusing on the importance of context itself. Further studies, under the influence of Foucault, developed this focus to include the idea that author, text and reader are constructed by discourses. A renewed awareness of how texts actually work and of the power inherent in all language, has led to the emergence of critical literacy. This research, working on the premise that practice often lags behind theory, examines constraints that may inhibit the development of critical literacy (through teaching with literature) in the New Zealand contexts of both secondary English (including classrooms with mainstreamed ESOL students) and ESOL (from a range of institutions). Two surveys, one for each teaching context, analyse teachers' reactions to concepts of reader-response theories with a view to determining the nature and prevalence of these constraints. The analysis reveals that in the mainstream context, contraints emerge in the areas of curriculum design (including examination and assessment procedures), teacher education, and students' receptivity while in the ESOL context, curriculum design and teacher development are significant. The ESOL context also reveals that there is a paucity of teaching with literature in language classrooms which means that the vehicle for the development of critical literacy, is denied students.
Keywords: Literacy -- Study and teaching; Reader-response criticism